PAIN IN DIABETES MELLITUS AND BRONCHOSCOPY PROCEDURES: BREAKTHROUGHS IN MANAGEMENT AND CARE - Lucas Nando Nugraha (Faculty of Medicine Universitas Kristen Duta Wacana, 2023)
Overall, these two studies provide valuable insights into efforts to reduce pain burden in patients with diabetes mellitus and patients undergoing bronchoscopic procedures. In the context of diabetes mellitus, understanding the characteristics of pain in patients can help in better management. Meanwhile, the use of music as a non-pharmacological therapy in bronchoscopy procedures shows potential to reduce pain and anxiety in patients. However, further research is needed to gain a deeper understanding, as well as to overcome existing limitations, and provide optimal benefits for patients.